Challenging post-conflict environments sustainable agriculture - Özerdem, Alpaslan; Roberts, Rebecca (Global security in a changing world, 2012)
By adopting a holistic multi-disciplinary approach which identifies key themes and case studies, this book sets the scene for the debate surrounding sustainable agriculture in post-conflict environments. Seeing 'fixing' agriculture as more than merely a technical matter, the volume focuses on this critical post-conflict challenge with social, political and cultural characteristics and consequences as well as the obvious economic ones.